Analisis Kinerja dan Strategi Pelaku UMKM di Tengah Pusaran Bisnis E-Commerce di Kota Gorontalo - Sitti Alwiya Lihawa (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the performance and strategies of Micro, Small, and Medium Enterprises (MSMEs) in the midst of e-commerce development, with a case study on BananaRoll_Au in Gorontalo City. The research method employed is qualitative, with data collected through in-depth interviews with the owner and employees. The findings reveal that BananaRoll_Au formulates its strategies based on three key factors: opportunities, human resources, and technology. The marketing strategies primarily focus on utilizing social media platforms such as WhatsApp, Facebook, and Instagram, which are considered effective in expanding market reach and attracting consumer interest. Moreover, social media use enables MSMEs to showcase products more appealingly while maintaining direct interaction with customers. These results indicate that the adoption of e-commerce and digital media plays a significant role in enhancing MSME performance, particularly in terms of promotion, customer service, and satisfaction. This research is expected to serve as a reference for other MSMEs in optimizing digital marketing strategies to improve competitiveness and ensure business sustainability in the modern business era.